Analisis Faktor – Faktor Yang Mempengaruhi Minat Wisata Berkunjung Di Kampung Coklat Kademangan Kabupaten Blitar - Nurul Farida (Universitas Islam Balitar, 2021)
This study aimed to determine the effect of service quality, perceived prize, location, and facilities either partially or simultaneously to visit tourist interest in “ Kampung Coklat”. The research is a quantitative, where to get data by survey and questionnaire as an instrument. The population as a whole study subjects were tourists visiting “Kampung coklat”. Sampels were taken from 100 people at random population. Test the validity of the instrument using Coeficient Correlation Pearson, and reliability testing using Cronbach Alpha. The Analisis Technique used is multiple regression analysis. Of research findings prove that, in partial service quality significantly influence buying interest with thitung (2.830) > ttabel (1,988) with a significance value (0006), and facilities significantly influence buying interest with thitung (4.859)> ttabel (1.988 ) with significant value (0.000). whereas the perception of price is partially no significant influence on buying interest with thitung (1589) < ttabel (1,988) with a significance value (0.115), and the location is partially not significantly influence buying interest with thitung (1229) < ttabel (1,988 ) with significant value (0222). And simultaneously the quality of service, perception of price, location, amenities and significant effect on buying interest with a value of Fhitung (29 909)> Ftabel (2,467) with a significance value (0.000)